(3agQSJ GdWhSjs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3TjQGRs)
(3ChdgG (B:s
(3GdMeO ddg hdj GdMeO heSJMbg(B... (3hHYO aEfj deG QCjJ LeGYI ef TjhN WGFaJfG ef CUMGH GdMOjK(B...s
(3BNQgG (B:s
(3GHf YUGe, dg fhGOQ, CNHQfG LeGYI Yf CHj GdeaVd Yf MejO Yf GHf YUGe(B. (3Je GdagQSJ(B...s
(3JHUQI GdYfhGf (B:s
(3GdagQSJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B84s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B72s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B225s
Keywords: (3GdJGQjNs